2003
DOI: 10.1086/377481
|View full text |Cite
|
Sign up to set email alerts
|

From Globular Clusters to Tidal Dwarfs: Structure Formation in the Tidal Tails of Merging Galaxies

Abstract: Using V and I images obtained with the Wide Field Planetary Camera 2 (WFPC2) of the Hubble Space Telescope, we investigate compact stellar structures within tidal tails. Six regions of tidal debris in the four classic "Toomre Sequence" mergers: NGC 4038/39 ("Antennae"), NGC 3256, NGC 3921, and NGC 7252 ("Atoms for Peace") have been studied in order to explore how the star formation depends upon the local and global physical conditions. These mergers sample a range of stages in the evolutionary sequence and tai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(123 citation statements)
references
References 66 publications
6
116
0
Order By: Relevance
“…5), which Tacconi et al (1999) found to display a velocity gradient and interpreted as due to a self-gravitating gas disc located in between the nuclei, is puzzling, since from merger simulations this is generally not expected to occur. We could be seeing a collapsed gas clump in a tidal arm -such features are found to occur quite often in simulations of merging galaxies above a certain gas fraction (Wetzstein et al 2007;Bournaud et al 2008), and are also seen in observations (Knierman et al 2003). An alternative, and perhaps more likely, interpretation of this gas concentration is a tidal bridge connecting the two nuclei that is viewed in projection.…”
Section: Merger Geometry and Stage And Cold Gas Concentrationsupporting
confidence: 53%
“…5), which Tacconi et al (1999) found to display a velocity gradient and interpreted as due to a self-gravitating gas disc located in between the nuclei, is puzzling, since from merger simulations this is generally not expected to occur. We could be seeing a collapsed gas clump in a tidal arm -such features are found to occur quite often in simulations of merging galaxies above a certain gas fraction (Wetzstein et al 2007;Bournaud et al 2008), and are also seen in observations (Knierman et al 2003). An alternative, and perhaps more likely, interpretation of this gas concentration is a tidal bridge connecting the two nuclei that is viewed in projection.…”
Section: Merger Geometry and Stage And Cold Gas Concentrationsupporting
confidence: 53%
“…Subsequent observations (Mirabel et al 1991;Hernquist 1992) and numerical simulations (Barnes & Hernquist 1992;Elmegreen et al 1993) demonstrated that the existence of dwarf galaxies as a result of a major interaction is possible. Since then and up until now, several observing campaigns have been launched in interacting systems, such as those in NGC 2782 (Yoshida et al 1994), Arp 105 (Duc & Mirabel 1994;Duc et al 1997), NGC 7252 (Hibbard et al 1994), NGC 5291 (Duc & Mirabel 1998;Higdon et al 2006), Arp 245 , small samples (Weilbacher et al 2000(Weilbacher et al , 2003Knierman et al 2003;Monreal-Ibero et al 2007), and Arp 305 (Hancock et al 2009). Hibbard & Mihos (1995) also developed a successful dynamical N-body model of NGC 7252.…”
Section: Introductionmentioning
confidence: 99%
“…Majewski (1994) reinvestigated this issue and added Sextans and perhaps Phoenix to the Fornax-Leo-Sculptor alignment, which is now known as the FL 2 S 2 plane. To explain the alignments, a common origin via the disruption of larger satellites orbiting in these planes is usually invoked, with the smaller dSph's forming as tidal condensations or broken-off fragments during the dynamical interaction between our Galaxy and a massive satellite (Kroupa 1997), much like the tidal dwarfs seen in extragalactic contexts (e.g., Knierman et al 2003). The parent satellite has been proposed to be the Large Magellanic Cloud (LMC) for the Magellanic plane and Fornax for the FL 2 S 2 plane (Lynden-Bell 1982).…”
Section: Introductionmentioning
confidence: 99%